Regions between challenges and unexpected opportunities - Cristina Bernini; Silvia Emili (FrancoAngeli, 2021)
Due to the Covid-19 pandemic, the XLI Annual Scientific Conference held on line in September 2-4, 2020. The Web Conference contributed to motivate the scientific debate on the regional challenges and opportunities in times of crisis. A large number of contributions have investigated the territorial impact of economic shocks and natural disaster and discussed possible trajectories for a sustainable regional development process. The book collects a selection of these contributions, covering different topics on the economic, social, and regional consequences of crises and recovery processes. The first part is dedicated specifically to the impact of the Covid-19 pandemic and to the ability of a territory to react. The challenges of the new pandemic came in addition to the economic and financial crises and the natural and environmental disasters that have occurred in recent decades. The second part then gathers contributions that discuss more broadly the resilience and regional responses to natural and economic shocks. Crises have largely affected the quality of life of citizens and may have compromised sustainable regional growth. To contribute to the discussion of these issues, the third part of the volume collects some studies that aim to analyse in depth the effects of crises in terms of individual and regional wellbeing, and their relationship with sustainability. The last part is dedicated to a discussion and empirical assessment of the role of regional and national policies in supporting recovery and resilience processes for regional development.
Keywords: 300